Photosynthetic production of the nitrogen-rich compound guanidine. Issue 11 (16th May 2019) - Wang, Bo; Dong, Tao; Myrlie, Aldon; Gu, Liping; Zhu, Huilan; Xiong, Wei; Maness, PinChing; Zhou, Ruanbao; Yu, Jianping
Abstract : Direct photosynthesis of the nitrogen-rich compound guanidine from CO2 and N2 . Abstract : The development of an sustainable economy calls for improved energy utilization and storage technologies. Although battery- and carbon-based routes have gained tremendous attention, nitrogen-based routes have rarely been exploited so far. Guanidine (CH5 N3 ) which contains 71.1% nitrogen by mass is an exemplary chemical to explore the nitrogen-based routes of energy utilization and storage. Guanidine has a variety of applications including its use as a slow-release fertilizer, a propellant, or as a precursor to pharmaceuticals and antimicrobial polymers. The conventional chemical synthesis of guanidine through the Frank–Caro process is energy-intensive, consumes fossil fuels, and is detrimental to the environment. Herein, a de novo guanidine biosynthesis (GUB) cycle is proposed with CO2 and nitrate/ammonium as the carbon and nitrogen sources, respectively. The ATP and NAD(P)H needed to drive the GUB cycle are generated via photosynthesis in an engineered cyanobacterium Synechocystis sp. PCC 6803 expressing an ethylene-forming enzyme (EFE). Up to 586.5 mg L −1 (9.9 mM) guanidine was produced after seven days of photoautotrophic cultivation, with an average productivity of 83.8 mg L −1 day −1 . In addition, guanidine was directly biosynthesized from CO2, N2 and H2 O in an engineered N2 -fixing cyanobacterium Anabaena sp. PCC 7120 expressing the EFE. This work demonstrates the first biological conversion of renewable solar energy into chemical energy stored in the nitrogen-rich compound guanidine, which could shed light on harnessing the biological nitrogen metabolism for energy utilization and storage.